Keabsahan Perkawinan Beda Agama Pasca Surat Edaran Mahkamah Agung Nomor 2 Tahun 2023: Studi Kasus Penetapan Nomor 423/Pdt.P/2023/PN.Jkt.Utr - Assegaf, Muhammad; Rato, Dominikus; Ali, Moh. (Acten Journal Law Review, 2024)
Marriage is a sacred and noble procession to build a household that is considered legitimate from a religious and state perspective. Positive law prohibits interfaith marriages as stated in SEMA No. 2 of 2023 concerning Judges' Instructions in Adjudicating Cases of Applications for Registration of Marriages Between People of Different Religions and Beliefs. However, the judge in Stipulation Number 423/PDT.P/2023/PN.Jkt.Utr granted the request for registration of interfaith marriage applications. The legal research used in this article is normative juridical, based on an internal perspective that is able to provide legal arguments when conflicts, ambiguities, or legal gaps are found. The results of the study show that the judge's considerations in Stipulation Number 423/PDT.P/2023/PN.Jkt.Utr are inappropriate in using the legal basis. The judge is of the view that Catholicism and Protestant Christianity are still within the same scope of faith so that they are in harmony. However, the judge did not refer to SEMA Number 2 of 2023 as a legal basis for deciding the case, did not consider the norm of Article 2 paragraph 1 of the Marriage Law, did not consider the rejection from the Dukcapil Office, did not consider evidence in the form of the Applicants' Identity Cards, and finally the Judge did not consider the prohibitions of each of the Applicants' religions. The Judge should have made a decision based on the correct legal basis as a consideration so that in the future there would be no more inappropriate decisions. Keywords : Marriage; Different Religion; Judge Consideration